Sharing Resources on the North Pacific Coast of North America: The Case of the Eulachon Fishery - Mitchell, Donald; Donald, Leland (Anthropologica, 2022)
Rights to exploit resource loci were usually owned in the Northwest Coast culture area and were normally held by descent groups. This was true of the right to fish for eulachon, a small, oil-rich, and highly valued anadromous fish which spawned in a limited number of river estuaries on the north Pacific coast of North America. At some of these spawning sites from 5 000 to 10 000 people assembled each spring, yet the participants did not form a political unit in any sense. In the absence of formal political structure, and despite frequent conflict, multicommunity exploitation of this rich resource was enabled by a shared concept of rights and traditional, informal, means of ending disputes.